![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
Solve the following equation: ${x^4} + \dfrac{8}{9}{x^2} + 1 = 3{x^3} + 3x$
Answer
513.9k+ views
Hint- Replace the value of x as its inverse in the given equation and proceed with sum and product of roots.
Given equation is \[{x^4} + \dfrac{8}{9}{x^2} + 1 = 3{x^3} + 3x \Rightarrow {x^4} + 3{x^3} + \dfrac{{8{x^2}}}{9} + 3x + 1 = 0{\text{ }} \to {\text{(1)}}\]
Let us replace \[x\] by \[\dfrac{1}{x}\] in the given equation, we get
\[{\left( {\dfrac{1}{x}} \right)^4} + \dfrac{8}{9}{\left( {\dfrac{1}{x}} \right)^2} + 1 = 3{\left( {\dfrac{1}{x}} \right)^3} + \dfrac{3}{x} \Rightarrow \dfrac{1}{{{x^4}}} + \dfrac{8}{{9{x^2}}} + 1 = \dfrac{3}{{{x^3}}} + \dfrac{3}{x}\]
Taking \[{\text{9}}{x^4}\] as the LCM on the LHS and \[{x^3}\] as the LCM on the RHS of the above equation
\[
\Rightarrow \dfrac{{9 + 8{x^2} + 9{x^4}}}{{9{x^4}}} = \dfrac{{3 + 3{x^2}}}{{{x^3}}} \Rightarrow \dfrac{{9 + 8{x^2} + 9{x^4}}}{{9x}} = 3 + 3{x^2} \Rightarrow \dfrac{{9 + 8{x^2} + 9{x^4}}}{9} = x\left( {3 + 3{x^2}} \right) \\
\Rightarrow 1 + \dfrac{{8{x^2}}}{9} + {x^4} = 3x + 3{x^3} \Rightarrow {x^4} + 3{x^3} + \dfrac{{8{x^2}}}{9} + 3x + 1 = 0 \\
\]
Clearly, the above equation which is obtained by replacing \[x\] by \[\dfrac{1}{x}\] in the given equation is the same as the given equation.
As, we know that in case of four degree polynomial (having two roots as \[\alpha \], \[\beta \]) if \[x\] is replaced by \[\dfrac{1}{x}\] and the fourth degree polynomial comes out to be same as the previous one then the other two roots of that polynomial will be \[\dfrac{1}{\alpha }\] and \[\dfrac{1}{\beta }\].
Also, for any general fourth degree polynomial \[a{x^4} + b{x^3} + c{x^2} + dx + e = 0\]
Sum of all the roots\[ = - \dfrac{b}{a}\]
Sum of product of different roots taken two at a time\[ = \dfrac{c}{a}\]
According to the given equation (1), we can say \[a = 1,{\text{ }}b = 3,{\text{ }}c = \dfrac{8}{9},{\text{ }}d = 3\] and \[e = 1\].
Therefore, Sum of all the roots of the given equation (1) is given by \[\alpha + \beta + \dfrac{1}{\alpha } + \dfrac{1}{\beta } = - \dfrac{3}{1} = - 3{\text{ }} \to {\text{(2)}}\]
Also, sum of product of different roots taken two at a time of the given equation (1) is given by
\[\alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\beta {\text{.}}\dfrac{1}{\beta }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{{\dfrac{8}{9}}}{1} = \dfrac{8}{9}\]
\[
\Rightarrow \alpha \beta {\text{ + }}1{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}1{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{8}{9} \Rightarrow \alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta } = \dfrac{8}{9} - 2 = - \dfrac{{10}}{9} \\
\Rightarrow \alpha \left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right){\text{ + }}\dfrac{1}{\alpha }\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - \dfrac{{10}}{9} \Rightarrow \left( {\alpha + \dfrac{1}{\alpha }} \right)\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - \dfrac{{10}}{9}{\text{ }} \to {\text{(3)}} \\
\]
Equation (2) can be rearranged as \[\left( {\alpha + \dfrac{1}{\alpha }} \right) = - 3 - \left( {\beta + \dfrac{1}{\beta }} \right)\]
Put the value of \[\left( {\alpha + \dfrac{1}{\alpha }} \right)\] in equation (3), we get
\[\left[ { - 3 - \left( {\beta + \dfrac{1}{\beta }} \right)} \right]\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - \dfrac{{10}}{9}\]
Let \[\left( {\beta + \dfrac{1}{\beta }} \right) = t\]
\[
\Rightarrow \left[ { - 3 - t} \right]t = - \dfrac{{10}}{9} \Rightarrow - \left( {3 + t} \right)t = - \dfrac{{10}}{9} \Rightarrow \left( {3 + t} \right)t = \dfrac{{10}}{9} \Rightarrow 9{t^2} + 27t - 10 = 0 \\
\Rightarrow 9{t^2} + 27t - 10 = 0 \Rightarrow 9{t^2} - 3t + 30t - 10 = 0 \Rightarrow 3t\left( {3t - 1} \right) + 10\left( {3t - 1} \right) = 0 \\
\Rightarrow \left( {3t - 1} \right)\left( {3t + 10} \right) = 0 \\
\]
i.e., Either \[3t - 1 = 0\] or \[3t + 10 = 0\]
\[
\Rightarrow t = \dfrac{1}{3} \Rightarrow \beta + \dfrac{1}{\beta } = \dfrac{1}{3} \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = \dfrac{1}{3} \Rightarrow 3{\beta ^2} + 3 = \beta \Rightarrow 3{\beta ^2} - \beta + 3 = 0 \Rightarrow \beta = \dfrac{{ - \left( { - 1} \right) \pm \sqrt {{{\left( { - 1} \right)}^2} - 4 \times 3 \times 3} }}{{2 \times 3}} \\
\Rightarrow \beta = \dfrac{{1 \pm \sqrt {1 - 36} }}{6} \Rightarrow \beta = \dfrac{{1 \pm \sqrt { - 35} }}{6} \Rightarrow \beta = \dfrac{{1 \pm i\sqrt {35} }}{6} \\
\]
or \[
t = - \dfrac{{10}}{3} \Rightarrow \beta + \dfrac{1}{\beta } = - \dfrac{{10}}{3} \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = - \dfrac{{10}}{3} \Rightarrow 3{\beta ^2} + 3 = - 10\beta \Rightarrow 3{\beta ^2} + 10\beta + 3 = 0 \Rightarrow 3{\beta ^2} + 9\beta + \beta + 3 = 0 \\
\Rightarrow 3\beta \left( {\beta + 3} \right) + 1\left( {\beta + 3} \right) = 0 \Rightarrow \left( {3\beta + 1} \right)\left( {\beta + 3} \right) = 0 \Rightarrow \beta = - \dfrac{1}{3}, - 3 \\
\]
Using equation (2) put the value of \[\beta \], we will get the value of \[\alpha \]
\[ \Rightarrow \alpha = - \dfrac{1}{3}, - 3\] or \[\alpha = \dfrac{{1 \pm i\sqrt {35} }}{6}\]
Therefore, all the roots of the given equation are \[ - \dfrac{1}{3}, - 3,\dfrac{{1 \pm i\sqrt {35} }}{6}\].
Note- These types of problems can be solved by somehow checking for some properties regarding roots of a polynomial and then finding out an appropriate relation between the roots and hence solving further to get the values of these roots.
Given equation is \[{x^4} + \dfrac{8}{9}{x^2} + 1 = 3{x^3} + 3x \Rightarrow {x^4} + 3{x^3} + \dfrac{{8{x^2}}}{9} + 3x + 1 = 0{\text{ }} \to {\text{(1)}}\]
Let us replace \[x\] by \[\dfrac{1}{x}\] in the given equation, we get
\[{\left( {\dfrac{1}{x}} \right)^4} + \dfrac{8}{9}{\left( {\dfrac{1}{x}} \right)^2} + 1 = 3{\left( {\dfrac{1}{x}} \right)^3} + \dfrac{3}{x} \Rightarrow \dfrac{1}{{{x^4}}} + \dfrac{8}{{9{x^2}}} + 1 = \dfrac{3}{{{x^3}}} + \dfrac{3}{x}\]
Taking \[{\text{9}}{x^4}\] as the LCM on the LHS and \[{x^3}\] as the LCM on the RHS of the above equation
\[
\Rightarrow \dfrac{{9 + 8{x^2} + 9{x^4}}}{{9{x^4}}} = \dfrac{{3 + 3{x^2}}}{{{x^3}}} \Rightarrow \dfrac{{9 + 8{x^2} + 9{x^4}}}{{9x}} = 3 + 3{x^2} \Rightarrow \dfrac{{9 + 8{x^2} + 9{x^4}}}{9} = x\left( {3 + 3{x^2}} \right) \\
\Rightarrow 1 + \dfrac{{8{x^2}}}{9} + {x^4} = 3x + 3{x^3} \Rightarrow {x^4} + 3{x^3} + \dfrac{{8{x^2}}}{9} + 3x + 1 = 0 \\
\]
Clearly, the above equation which is obtained by replacing \[x\] by \[\dfrac{1}{x}\] in the given equation is the same as the given equation.
As, we know that in case of four degree polynomial (having two roots as \[\alpha \], \[\beta \]) if \[x\] is replaced by \[\dfrac{1}{x}\] and the fourth degree polynomial comes out to be same as the previous one then the other two roots of that polynomial will be \[\dfrac{1}{\alpha }\] and \[\dfrac{1}{\beta }\].
Also, for any general fourth degree polynomial \[a{x^4} + b{x^3} + c{x^2} + dx + e = 0\]
Sum of all the roots\[ = - \dfrac{b}{a}\]
Sum of product of different roots taken two at a time\[ = \dfrac{c}{a}\]
According to the given equation (1), we can say \[a = 1,{\text{ }}b = 3,{\text{ }}c = \dfrac{8}{9},{\text{ }}d = 3\] and \[e = 1\].
Therefore, Sum of all the roots of the given equation (1) is given by \[\alpha + \beta + \dfrac{1}{\alpha } + \dfrac{1}{\beta } = - \dfrac{3}{1} = - 3{\text{ }} \to {\text{(2)}}\]
Also, sum of product of different roots taken two at a time of the given equation (1) is given by
\[\alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\beta {\text{.}}\dfrac{1}{\beta }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{{\dfrac{8}{9}}}{1} = \dfrac{8}{9}\]
\[
\Rightarrow \alpha \beta {\text{ + }}1{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}1{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{8}{9} \Rightarrow \alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta } = \dfrac{8}{9} - 2 = - \dfrac{{10}}{9} \\
\Rightarrow \alpha \left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right){\text{ + }}\dfrac{1}{\alpha }\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - \dfrac{{10}}{9} \Rightarrow \left( {\alpha + \dfrac{1}{\alpha }} \right)\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - \dfrac{{10}}{9}{\text{ }} \to {\text{(3)}} \\
\]
Equation (2) can be rearranged as \[\left( {\alpha + \dfrac{1}{\alpha }} \right) = - 3 - \left( {\beta + \dfrac{1}{\beta }} \right)\]
Put the value of \[\left( {\alpha + \dfrac{1}{\alpha }} \right)\] in equation (3), we get
\[\left[ { - 3 - \left( {\beta + \dfrac{1}{\beta }} \right)} \right]\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - \dfrac{{10}}{9}\]
Let \[\left( {\beta + \dfrac{1}{\beta }} \right) = t\]
\[
\Rightarrow \left[ { - 3 - t} \right]t = - \dfrac{{10}}{9} \Rightarrow - \left( {3 + t} \right)t = - \dfrac{{10}}{9} \Rightarrow \left( {3 + t} \right)t = \dfrac{{10}}{9} \Rightarrow 9{t^2} + 27t - 10 = 0 \\
\Rightarrow 9{t^2} + 27t - 10 = 0 \Rightarrow 9{t^2} - 3t + 30t - 10 = 0 \Rightarrow 3t\left( {3t - 1} \right) + 10\left( {3t - 1} \right) = 0 \\
\Rightarrow \left( {3t - 1} \right)\left( {3t + 10} \right) = 0 \\
\]
i.e., Either \[3t - 1 = 0\] or \[3t + 10 = 0\]
\[
\Rightarrow t = \dfrac{1}{3} \Rightarrow \beta + \dfrac{1}{\beta } = \dfrac{1}{3} \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = \dfrac{1}{3} \Rightarrow 3{\beta ^2} + 3 = \beta \Rightarrow 3{\beta ^2} - \beta + 3 = 0 \Rightarrow \beta = \dfrac{{ - \left( { - 1} \right) \pm \sqrt {{{\left( { - 1} \right)}^2} - 4 \times 3 \times 3} }}{{2 \times 3}} \\
\Rightarrow \beta = \dfrac{{1 \pm \sqrt {1 - 36} }}{6} \Rightarrow \beta = \dfrac{{1 \pm \sqrt { - 35} }}{6} \Rightarrow \beta = \dfrac{{1 \pm i\sqrt {35} }}{6} \\
\]
or \[
t = - \dfrac{{10}}{3} \Rightarrow \beta + \dfrac{1}{\beta } = - \dfrac{{10}}{3} \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = - \dfrac{{10}}{3} \Rightarrow 3{\beta ^2} + 3 = - 10\beta \Rightarrow 3{\beta ^2} + 10\beta + 3 = 0 \Rightarrow 3{\beta ^2} + 9\beta + \beta + 3 = 0 \\
\Rightarrow 3\beta \left( {\beta + 3} \right) + 1\left( {\beta + 3} \right) = 0 \Rightarrow \left( {3\beta + 1} \right)\left( {\beta + 3} \right) = 0 \Rightarrow \beta = - \dfrac{1}{3}, - 3 \\
\]
Using equation (2) put the value of \[\beta \], we will get the value of \[\alpha \]
\[ \Rightarrow \alpha = - \dfrac{1}{3}, - 3\] or \[\alpha = \dfrac{{1 \pm i\sqrt {35} }}{6}\]
Therefore, all the roots of the given equation are \[ - \dfrac{1}{3}, - 3,\dfrac{{1 \pm i\sqrt {35} }}{6}\].
Note- These types of problems can be solved by somehow checking for some properties regarding roots of a polynomial and then finding out an appropriate relation between the roots and hence solving further to get the values of these roots.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The area of a 6m wide road outside a garden in all class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is the electric flux through a cube of side 1 class 10 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
The radius and height of a cylinder are in the ratio class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Why is there a time difference of about 5 hours between class 10 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Change the following sentences into negative and interrogative class 10 english CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Write a letter to the principal requesting him to grant class 10 english CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Write an application to the principal requesting five class 10 english CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)